2018
DOI: 10.1016/j.cell.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Switches BAF Complexes to Protect β Cells

Abstract: A primary cause of disease progression in type 2 diabetes (T2D) is β cell dysfunction due to inflammatory stress and insulin resistance. However, preventing β cell exhaustion under diabetic conditions is a major therapeutic challenge. Here, we identify the vitamin D receptor (VDR) as a key modulator of inflammation and β cell survival. Alternative recognition of an acetylated lysine in VDR by bromodomain proteins BRD7 and BRD9 directs association to PBAF and BAF chromatin remodeling complexes, respectively. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
173
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(181 citation statements)
references
References 65 publications
(77 reference statements)
7
173
0
1
Order By: Relevance
“…However, it is easy to envision that the accessibility profile of immortalized cells could be substantially different from that of normal cells. In addition, the interactions of VDR with different chromatin remodelers (Nurminen et al, 2018(Nurminen et al, , 2019Pereira et al, 2011;Wei et al, 2018) support the potential role of VDR as a pioneer factor.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, it is easy to envision that the accessibility profile of immortalized cells could be substantially different from that of normal cells. In addition, the interactions of VDR with different chromatin remodelers (Nurminen et al, 2018(Nurminen et al, , 2019Pereira et al, 2011;Wei et al, 2018) support the potential role of VDR as a pioneer factor.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown the capacity of VDR to interact with a range of TFs including PU.1 and GABPA, and with chromatin remodeling and histone modification enzymes such as BRD7 and KDM6B (Pereira et al, 2011;Seuter et al, 2017Seuter et al, , 2018Wei et al, 2018). There is some evidence that vitamin D may induce DNA methylation alterations (Doig et al, 2013;O'Brien et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, vitamin D has a beneficial role in pancreatic β‐cell function as well as hepatic lipid and glucose metabolism by increasing intracellular Ca +2 in insulin‐resistant states. Notably, a recent report showed that pharmacological potentiation of vitamin D receptor signalling partially restores β‐cell function and glucose homeostasis in type 2 diabetes mouse models; thus, we cannot exclude the possibility that the changes in metabolic variables and insulin sensitivity observed in K ATP ‐GOF‐R mice were promoted by differential vitamin D and calcium handling. Together, these results suggest that intermediate factors other than glucose metabolism could increase [Ca 2+ ] i and promote insulin secretion in K ATP ‐GOF‐R mice.…”
Section: Discussionmentioning
confidence: 99%
“…1,25(OH) 2 D 3 acts as a high‐affinity ligand that binds to the vitamin D receptor (VDR), which is found in most cells of the body to carry out its diverse set of functions. Activated VDR controls the expression of genes by functioning as a transcription factor, and as an epigenetic regulator through its direct acetylation and control of chromatin structure via interactions with the PBAF/BAF chromatin remodelling complex (Figure ). As a liganded transcription factor, the VDR can interact with specific DNA sequences termed VDR response elements (VDREs).…”
Section: Vitamin Dmentioning
confidence: 99%